Hydrogeochemical characterization of groundwater in a coastal area, central western Senegal - Ndoye, Seyni; Diedhiou, Mathias; Celle, Helene; Faye, Serigne; Baalousha, Mohammed; Le Coustumer, Philippe (Frontiers in Water, 2023)
This study aims to determine the main factors and mechanisms controlling groundwater chemistry in a coastal area. Hydrogeochemical (Piper and Chadha diagrams, chloroalkaline indices, normalized bivariate plots) and multivariate statistical (Hierarchical cluster analyses) techniques were used to identify the processes controlling the groundwater hydrochemistry and groundwater types. Forty-two groundwater samples were collected and analysed for concentrations of major and some minor ions, electrical conductivity (EC), total dissolved solids (TDS), temperature, and pH. Average pH of groundwater is 7.6. Approximately, 80% of the groundwater samples have a TDS less than 1000 mg/L and EC values are very heterogeneous. These quality parameters indicate that the water samples are neutral freshwater. The dominant water types in the study area are Na-Cl water type, Ca-Mg-HCO3, and mixed Ca-Mg-Cl due to fresh water/salt water contact in the presence of clay. Chloroalkaline indices and normalized bivariate plots show that the chemistry of groundwater is controlled mainly by water-rock interaction and evaporation processes. As water-rock interaction processes, dissolution of carbonate and evaporite, weathering of silicate, ions exchange regulates major ion chemistry.